Corpus-Based Reflective Practice for Professional Development: A Collaborative Micro Auto-Ethnography - Olcay Sert; Elisabeth Wulff Sahlén; Thorsten Schröter (Education Sciences)
Recent research underscores the significance of data-led and collaborative reflection in enhancing teaching practices and professional development of teachers. While video-based reflections have been extensively studied, the potential of corpus-based methods remains underexplored. We address this gap in two ways. Firstly, we describe a research and development project in which we employed a corpus linguistic tool to analyse and reflect on our own lectures, with the ulterior aim of promoting a corpus-based reflective practice (CBRP) model that would help other teachers do the same. Secondly, we introduce collaborative micro auto-ethnography (CMAE) to illustrate how our model can facilitate the noticing of different aspects of teacher talk and lead to, what we call, snowball reflections (i.e., a sequence of reflective talk that extends a topic and spreads from one participant to the next). Our approach shows that corpus analysis, coupled with collaborative reflections, has the potential to not only enhance language use but also stimulate broader and deeper pedagogical discussions on and insights into teaching styles and student engagement, going beyond analyses of single words and lexico-grammatical patterns in teacher talk. We argue that there should be institutional support for developing new corpus-based professional development initiatives and that researchers can benefit from using ethnographic data together with detailed analyses of interactions.